2020
DOI: 10.1111/tpj.14634
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a large photosystem I–light‐harvesting complex II supercomplex with an additional Lhca1–a4 dimer in Arabidopsis

Abstract: The biological conversion of light energy into chemical energy is performed by a flexible photosynthetic machinery located in the thylakoid membranes. Photosystems I and II (PSI and PSII) are the two complexes able to harvest light. PSI is the last complex of the electron transport chain and is composed of multiple subunits: the proteins building the catalytic core complex that are well conserved between oxygenic photosynthetic organisms, and, in green organisms, the membrane light-harvesting complexes (Lhc) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Unlike PSII, where changes in antenna size have been consistently observed, the LHCI antenna size of PSI has been reported to be unaffected by changes in light intensity in some studies (Ballottari et al ., 2007; Albanese et al ., 2018), but altered in another (Bailey et al ., 2001). Indeed, a recent study showed that PSI in Arabidopsis can bind additional copies of LHCA1 and 4 (Crepin et al ., 2020), suggesting the antenna size can undergo acclimation. Consistent with this suggestion, we observed a 10–20% increase in LHCA1 and 3 in LL compared to ML but no significant change in HL (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike PSII, where changes in antenna size have been consistently observed, the LHCI antenna size of PSI has been reported to be unaffected by changes in light intensity in some studies (Ballottari et al ., 2007; Albanese et al ., 2018), but altered in another (Bailey et al ., 2001). Indeed, a recent study showed that PSI in Arabidopsis can bind additional copies of LHCA1 and 4 (Crepin et al ., 2020), suggesting the antenna size can undergo acclimation. Consistent with this suggestion, we observed a 10–20% increase in LHCA1 and 3 in LL compared to ML but no significant change in HL (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…are not observed in the structures but are present in the membranes, but their exact position is unknown. The Lhca1 and Lhca4 observed by Crepin et al (2020) in some of the PSI particles are represented in lighter shades of green. The arrows indicate the locations of PSII and PSI in the grana and stroma lamellae, respectively.…”
Section: The Antenna Size Of Photosystem Imentioning
confidence: 99%
“…The Lhca1 and Lhca4 observed by Crepin et al . (2020) in some of the PSI particles are represented in lighter shades of green. The arrows indicate the locations of PSII and PSI in the grana and stroma lamellae, respectively.…”
Section: The Antenna Size Of Photosystem IImentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, an additional Lhca1/Lhca4 dimer bound to PsaH side was recently found in Arabidopsis. 78 (For a recent review on the supercomplex diversity, see ref. 79 and 80.)…”
Section: Psi-lhci Subunits and Protein Supercomplexesmentioning
confidence: 99%